The Royal Ballet in House Photographs by Bill Cooper. Review. - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2003)
Book review. PALABRAS CLAVE: photographer Bill Cooper, Royal Ballet, dance photo book.
Dentro del apartado "Off the Shelf".
The Royal Ballet in House: Photographs by Bill Cooper. Oberon Books.